Fiber bragg grating-based fabry-perot interferometer sensor for damage detection on thin aluminum plate - Nurazima, Ismail; Z. M., Hafizi; Ooi, Cheong-Weng; Muhammad Khairol Annuar, Zaini; Che Ku Eddy Nizwan, Che Ku Husin; Lim, Kok-Sing; Harith, Ahmad (IEEE, 2020)
Structural Health Monitoring of engineering structures has become an essential measure for the prevention of catastrophic failures. This study presented a feasibility study of Fiber Bragg Grating-based Fabry-Perot interferometer (FBG-FPI) sensor for damage detection on an aluminum plate, by acoustic Lamb wave technique. In the investigation, a rectangular damage slot was introduced to the plate, at 15 cm from the actuator. Two FBG-FPI sensors were surface-mounted on the aluminum plate for the detection. In the analysis, we observed an additional wave packet with attenuated amplitude and time delay in the time-domain signal for the defect plate. Similar features are observed in the time-frequency spectrograms and they are important signatures that can be used for detecting the defect. The findings show the applicability of FBG-FPI sensor for damage detection on a thin-walled metallic structure.